Interpretive monitoring in the caudate nucleus - Yanike, Marianna (eLife, 2014)
In a dynamic environment an organism has to constantly adjust ongoing behavior to adapt to a given context. This process requires continuous monitoring of ongoing behavior to provide its meaningful interpretation. The caudate nucleus is known to have a role in behavioral monitoring, but the nature of these signals during dynamic behavior is still unclear. We recorded neuronal activity in the caudate nucleus in monkeys during categorization behavior that changed rapidly across contexts. We found that neuronal activity maintained representation of the identity and context of a recently categorized stimulus, as well as interpreted the behavioral meaningfulness of the maintained trace. The accuracy of this cognitive monitoring signal was highest for behavior for which subjects were prone to make errors. Thus, the caudate nucleus provides interpretive monitoring of ongoing behavior, which is necessary for contextually specific decisions to adapt to rapidly changing conditions. DOI: http://dx.doi.org/10.7554/eLife.03727.001